Theoretical investigation of the performance of integrated seawater desalination plant utilizing renewable energy. (15th October 2016) - Ismail, Tamer M.; Azab, A.K.; Elkady, M.A.; Abo Elnasr, M.M.
Highlights: Integrated desalination plant consisting of MED and MVC is investigated. A theoretical model was employed using the MATLAB software. A parametric analysis was conducted to elaborate the important factors affect the plant. Results indicate that the site selection plays a very important role in desalination. Solar intensity and water salinity are the most factors in assessing the collector area. Abstract: In the present work, theoretical investigation of the performance of two sequential desalination systems, multi-effect distillation and mechanical vapor compression, is carried out. A mathematical model is developed and implemented in MATLAB and validated by results available in the literature. Then the parametric analysis is carried out to produce distillate water and salt utilizing renewable energy. A parametric analysis has been conducted to understand the important factors that affect the performance of the plant. Furthermore, three sites are selected in Egypt (Marsa Matrouh, Ras Benas, and Taba) and economic feasibility of the proposed desalination system is carried out and compared with plant economy of conventional fossil fuels. The results show that site location, solar intensity, wind speed, ambient temperature, and water salinity are the most dominant factors in the performance.